Coordination of spinal motion in the transverse and frontal planes during walking in people with and without recurrent low back pain - Crosbie, Jack; De Faria Negrão Filho, Ruben [UNESP]; Nascimento, Dafne Port; Ferreira, Paulo (Wolters Kluwer, 2013)
STUDY DESIGN. Observational cohort study. OBJECTIVE. To investigate spinal coordination during preferred and fast speed walking in pain-free subjects with and without a history of recurrent low back pain (LBP). SUMMARY OF BACKGROUND DATA. Dynamic motion of the spine during walking is compromised in the presence of back pain (LBP), but its analysis often presents some challenges. The coexistence of significant symptoms may change gait because of pain or adaptation of the musculoskeletal structures or both. A history of LBP without the overlay of a current symptomatic episode allows a better model in which to explore the impact on spinal coordination during walking. METHODS. Spinal and lower limb segmental motions were tracked using electromagnetic sensors. Analyses were conducted to explore the synchrony and spatial coordination of the segments and to compare the control and subjects with LBP. RESULTS. We found no apparent differences between the groups for either overall amplitude of motion or most indicators of coordination in the lumbar region; however, there were significant postural differences in the mid-stance phase and other indicators of less phase locking in controls compared with subjects with LBP. The lower thoracic spinal segment was more affected by the history of back pain than the lumbar segment. CONCLUSION. Although small, there were indicators that alterations in spinal movement and coordination in subjects with recurrent LBP were due to adaptive changes rather than the presence of pain. © 2013, Lippincott Williams & Wilkins.
Keywords: Coordination; Gait; Kinematics; Movement control; Recurrent back pain; Spine; Synchrony; adult; amplitude modulation; clinical article; cohort analysis; controlled study; electromagnetic field; female; human; leg; low back pain; lumbar spine; male; motor coordination; observational study; priority journal; recurrent disease; spatial analysis; spine mobility; thoracic spine; walking speed; Adaptation, Physiological; Adult; Analysis of Variance; Biomechanics; Case-Control Studies; Disability Evaluation; Electromagnetic Phenomena; Female; Fourier Analysis; Hip Joint; Humans; Low Back Pain; Lumbar Vertebrae; Male; Middle Aged; Pain Measurement; Posture; Range of Motion, Articular; Recurrence; Thoracic Vertebrae; Walking; Young Adult